2012
DOI: 10.1161/circheartfailure.112.966580
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Remodeling in Response to Long-Term Exposure to Fine Particulate Matter Air Pollution

Abstract: Background Air pollution is a pervasive environmental health hazard that occurs over a lifetime of exposure in individuals from many industrialized societies. However, studies have focused primarily on exposure durations that correspond to only a portion of the lifespan. We therefore tested the hypothesis that exposure over a considerable portion of the lifespan would induce maladaptive cardiovascular responses. Methods and Results C57BL/6 male mice were exposed to concentrated ambient particles <2.5 μm (par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(152 citation statements)
references
References 58 publications
8
127
3
7
Order By: Relevance
“…Pregnancy was confirmed and time-dated with the presence of a vaginal plug. Dams were exposed to concentrated PM2.5 from the Columbus, OH region using the OASIS-1 aerosol concentration system, which has been previously described (47). Dams were placed into the exposure system for 6 h a day, 7 days a wk, separated into either PM 2.5 exposure or air that has been filtered by a high-efficiency air filter (FA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnancy was confirmed and time-dated with the presence of a vaginal plug. Dams were exposed to concentrated PM2.5 from the Columbus, OH region using the OASIS-1 aerosol concentration system, which has been previously described (47). Dams were placed into the exposure system for 6 h a day, 7 days a wk, separated into either PM 2.5 exposure or air that has been filtered by a high-efficiency air filter (FA).…”
Section: Methodsmentioning
confidence: 99%
“…Cardiomyocytes were isolated as previously described (33,42,43,46,47). Briefly, hearts were removed and retrogradely perfused through the aorta with Liberase and trypsin until digested.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory (84) demonstrated that mice exposed to concentrated PM 2.5 over a period of 9 mo demonstrated decreased cardiac function. Male mice that were exposed to PM 2.5 showed higher rates of cardiac remodeling characterized by increases in both left ventricular end-systolic and enddiastolic diameters compared with filtered air-exposed control mice.…”
Section: Animal Modelsmentioning
confidence: 76%
“…Several studies conducted in Europe and America have shown that air pollution is associated with cardiovascular and respiratory deaths and hospital admissions. Although more studies have focused on the respiratory system as the main target of air pollution adverse effects, but recent evidence has shown that air pollution can also affect the cardiovascular system and particularly lead to ischemic heart diseases [12][13][14] . The harmful effects of increasing concentrations of particulate matter (PM) and carbon monoxide and other pollutants has been demonstrated as an increase in hospital emergency admissions for respiratory diseases in several studies [15] .…”
Section: Introductionmentioning
confidence: 99%